Screening for obstructive sleep apnea syndrome in asthma patients: a prospective study based on Berlin and STOP-Bang questionnaires - Lu, Huan; Fu, Cuiping; Li, Wenjing; Jiang, Hong; Wu, Xiaodan; Li, Shanqun (Journal of Thoracic Disease, 2017)
Background: The bidirectional relationship of asthma and obstructive sleep apnea (OSA) has been confirmed in recent years. However, in the clinical practice, majority of asthma patients did not pay adequate attention to their sleep apnea condition. Berlin questionnaire (BQ) and STOP-Bang questionnaire (SBQ) are two most common OSA screening questionnaires to screen high-risk patients for OSA. This study aimed at evaluating the predictive performance of BQ and SBQ for OSA in asthma patients. Methods: Asthma outpatients of Zhongshan Hospital were enrolled into the study. All patients were asked to fill in the BQ and SBQ and clinical characteristics and asthma characteristics were recorded. Univariate and multivariate logistic regression analyses were applied to identify risk factors of OSA in asthma patients. With the gold standard of laboratory-based overnight polysomnography (PSG), the predictive performance of SBQ and BQ was evaluated and compared. The probability of OSA severity was predicted by various SBQ scores in asthma patients. Results: A total of 123 asthma patients (average age 47.56±12.12 years; 57.72% males) were enrolled and underwent PSG diagnosis overnight at Sleep Center. Logistic regression analyses showed that rhinitis (adjusted OR =4.30; 95% CI: 1.50–12.37, P=0.007) and dyslipidemia (adjusted OR =2.75; 95% CI: 1.16–6.51, P=0.021) were associated with OSA in asthma patients after adjusting for known OSA risk factors. No asthma functional characteristic differences were found to be associated with OSA severity in the study. The prevalence of moderate-to-severe OSA (AHI ≥15) in the asthmatic population sample was 36.59% (45/123). Questionnaires predictive results showed that compared with BQ, SBQ has higher diagnostic sensitivity (84.4% vs. 60%), lower specificity (79.5% vs. 91%) lower positive predictive value (PPV): (70.4% vs. 79.4%) and higher negative predictive value (NPV) (90% vs. 80%) to detect moderate-to-severe OSA at the cut-off as AHI of 15/h. OSA probability results showed that with the increasing of the questionnaire scores, the moderate and severe OSA probability of SBQ rose significantly. Conclusions: SBQ is a preferable sleep questionnaire better than BQ for detecting moderate and severe OSA in asthma patients which should be validated in larger population sample.